Urbanism and Animal Exploitation in Southwest Highland Iran, 3400-1500 B.C. - Zeder, Melinda Ann (1985)
Ph.D. Dissertation. 2 vols.; Chairman: Henry T. Wright. Order No. DA8600586; cf. DissAbstr 46/11 (May 1986) 3393-A/3394-A.